2011
DOI: 10.1158/1078-0432.ccr-10-2491
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Oxidative Damage Repair GenesNUDT1,OGG1, andMUTYHin Patients from Mismatch Repair Proficient HNPCC Families (MSS-HNPCC)

Abstract: Purpose: Several studies have described molecular differences between microsatellite stable hereditary nonpolyposis colorectal cancer (MSS-HNPCC) and microsatellite unstable Lynch syndrome tumors (MSI-HNPCC). These differences highlight the possibility that other instability forms could explain cancer susceptibility in this group of families.The base excision repair (BER) pathway is the major DNA repair pathway for oxidative DNA damage. A defect in this pathway can result in DNA transversion mutations and a su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 49 publications
4
32
1
Order By: Relevance
“…All variants are named according to the Human Genome Variation Society (HGVS) and to the reference transcript NM_000059 3. Variants were classified according to their pathogenicity risk.…”
mentioning
confidence: 99%
“…All variants are named according to the Human Genome Variation Society (HGVS) and to the reference transcript NM_000059 3. Variants were classified according to their pathogenicity risk.…”
mentioning
confidence: 99%
“…The only variant identified in the OGG1 gene (NM_016821.2) with a population MAF < 1% was c.137G>A (p.R46Q) (rs104893751; MAF GnomAD = 0.22% (600/275,590)). It had been previously shown that this variant might affect splicing causing the insertion of intron 1 (Garre et al., ; Kohno et al., ), having been associated with CRC predisposition when occurring in the germline (Garre et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we sought to determine changes in stress response proteins in β2-M knockdown prostate cancer cells. Using C4-2B control and β2-M knockdown prostate cancer cells (KD β2-M ) we tested the levels of stress response proteins such as heat shock protein 27 (HSP27) 17 and heat shock protein 70 (HSP70) 18 and DNA repair enzymes such as N-methylpurine-DNA glycosylase (MPG) 19 and nudix (nucleoside diphosphate linked moiety X)-type motif 1 (NUDT1) 20. Interestingly, the stress response and heat shock proteins were downregulated in β2-M knockdown clones KD β2-M (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%